Dual inhibition of Wnt and Yes‐associated protein signaling retards the growth of triple‐negative breast cancer in both mesenchymal and epithelial states. Issue 4 (21st February 2018) - Sulaiman, Andrew; McGarry, Sarah; Li, Li; Jia, Deyong; Ooi, Sarah; Addison, Christina; Dimitroulakos, Jim; Arnaout, Angel; Nessim, Carolyn; Yao, Zemin; Ji, Guang; Song, Haiyan; et al.
Abstract : Triple‐negative breast cancer (TNBC), the most refractory subtype of breast cancer to current treatments, accounts disproportionately for the majority of breast cancer‐related deaths. This is largely due to cancer plasticity and the development of cancer stem cells (CSCs). Recently, distinct yet interconvertible mesenchymal‐like and epithelial‐like states have been revealed in breast CSCs. Thus, strategies capable of simultaneously inhibiting bulk and CSC populations in both mesenchymal and epithelial states have yet to be developed. Wnt/β‐catenin and Hippo/YAP pathways are crucial in tumorigenesis, but importantly also possess tumor suppressor functions in certain contexts. One possibility is that TNBC cells in epithelial or mesenchymal state may differently affect Wnt/β‐catenin and Hippo/YAP signaling and CSC phenotypes. In this report, we found that YAP signaling and CD44 high /CD24 −/low CSCs were upregulated while Wnt/β‐catenin signaling and ALDH+ CSCs were downregulated in mesenchymal‐like TNBC cells, and vice versa in their epithelial‐like counterparts. Dual knockdown of YAP and Wnt/β‐catenin, but neither alone, was required for effective suppression of both CD44 high /CD24 −/low and ALDH+ CSC populations in mesenchymal and epithelial TNBC cells. These observations were confirmed with cultured tumor fragments prepared from patients with TNBC after treatment with Wnt inhibitor ICG‐001 and YAP inhibitor simvastatin. In addition, a clinical database showed that decreased gene expression of Wnt and YAP was positively correlated with decreased ALDH and CD44 expression in patients' samples while increased patient survival. Furthermore, tumor growth of TNBC cells in either epithelial or mesenchymal state was retarded, and both CD44 high /CD24 −/low and ALDH+ CSC subpopulations were diminished in a human xenograft model after dual administration of ICG‐001 and simvastatin. Tumorigenicity was also hampered after secondary transplantation. These data suggest a new therapeutic strategy for TNBC via dual Wnt and YAP inhibition. Abstract : Wnt/β‐catenin and Hippo/YAP pathways are crucial in tumorigenesis, but also possess tumor suppressor functions in certain contexts. We show here that epithelial and mesenchymal TNBC displayed differential Wnt and YAP signaling and CSC phenotypes. Dual inhibition of YAP and Wnt/β‐catenin, but neither alone effectively suppresses CD44 high /CD24 −/low and ALDH + CSC subpopulations and tumorigenesis in mesenchymal or epithelial state.